Analyzing the Impact of Product Innovation and Digital Marketing on Enhancing Competitive Advantages in Sasirangan Cloth MSMEs - Irma Safitri Katuuk; Anna Nur Faidah; M. Zainal Abidin; Ahmad Rifani (At-Tadbir : jurnal ilmiah manajemen, 2023)
This study explores the impact of product innovation and digital marketing on the competitive advantage of MSMEs in Banjarmasin. Employing a quantitative approach with 45 MSMEs as the population, the research uses a saturated sampling technique for data collection through a structured questionnaire. Multiple linear regression analysis is employed for data analysis. The findings indicate that product innovation positively and significantly influences the competitive advantage of Sasirangan Kain MSMEs in Banjarmasin, allowing them to differentiate and gain an edge over competitors. Additionally, digital marketing significantly contributes to their competitive advantage by effectively reaching target customers and fostering a strong brand presence. Emphasizing continuous innovation and adopting digital marketing strategies are crucial for achieving sustainable competitive advantages in this market. Policymakers and MSMEs should prioritize these aspects to thrive in the dynamic business landscape. These research findings offer valuable insights, highlighting the significance of product innovation and digital marketing as essential drivers of competitive advantage for MSMEs in Banjarmasin.